2022
DOI: 10.1002/mar.21769
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of self‐disclosure to promotional response: Examining the roles of deservingness and social class

Abstract: Facing the fact of declining sales of firms, promotions serve as an important tool to facilitate short-term sales. Yet, marketers still face the question of promotion effectiveness based on consumer self-disclosure behavior. In this paper, we examine the effects of self-relevant information disclosure on promotional response as well as the mechanism and boundary conditions associated with this effect. Four studies using both real and fictitious brands across a variety of contexts were conducted to test the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 92 publications
(204 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, researchers have extensively investigated the effect of self‐disclosure in various contexts (Huang, 2016; Lei et al, 2023; Liu & Brown, 2014; Wang et al, 2023). Wang et al (2023) found that self‐disclosure boosts promotional responses by creating a sense of deservingness in the retailing context.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, researchers have extensively investigated the effect of self‐disclosure in various contexts (Huang, 2016; Lei et al, 2023; Liu & Brown, 2014; Wang et al, 2023). Wang et al (2023) found that self‐disclosure boosts promotional responses by creating a sense of deservingness in the retailing context.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, researchers have extensively investigated the effect of self‐disclosure in various contexts (Huang, 2016; Lei et al, 2023; Liu & Brown, 2014; Wang et al, 2023). Wang et al (2023) found that self‐disclosure boosts promotional responses by creating a sense of deservingness in the retailing context. Postpartum moms’ superficial and personal level disclosures on social media have a favorable effect on the online social support they receive, which reduces depressive mood (Lei et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatedly, Söderlund (2020) also explored the outcomes of encouraging customers to reveal personal information in the context of movie recommendation services and demonstrated that asking customers to share personal information has a positive (negative) effect on customer satisfaction when customers perceive the increased customization (privacy concerns) of the service. More recently, Wang et al (2022) showed that customers' self‐disclosure increases their promotional response because customers perceive that they deserve more special treatment.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%